The China shock impact on labor informality: The effects on Brazilian manufacturing workers - Lourenço Senne Paz (Economies, 2022)
The vigorous growth of the Chinese economy together with its increasingly successful role in international trade may have profoundly impacted developing countries. This study examines the large increase in the international trade exposure of the Brazilian economy during 2000-2012 to assess the impacts of import competition on its manufacturing formal and informal labor markets. In this period, import penetration grew by more than 20 percent in Brazil, and the share of the import penetration originating in China increased from 3 to 20 percent. At the same time, the share of informal workers in manufacturing declined from 27 to approximately 15 percent. Employing a switching regression model and Brazilian household survey data, this study finds that a greater industry-level Chinese and 'rest of the world' import penetration increases the likelihood of jobs becoming informal at different intensities, and these effects are smaller in unskilled-labor intensive industries and manufacturing states. Additionally, both types of import penetration positively impact the average informal wage. In contrast, the estimates suggest that a larger Chinese import penetration reduces average formal wages, while imports from elsewhere have the opposite effect. The results also indicate that the magnitude of the effects on wages are moderated by the unskilled labor intensity of the industry and whether the worker is located in a manufacturing state.
Keywords: 330; Brazil; China; import penetration; informal labor markets; wages